Analisis Jalur Faktor-faktor yang Mempengaruhi Perilaku Pencegahan Stunting Menggunakan Health Promotion Model - Valentina Dili Ariwati; Qonitah Khalda (LPPM STIKES Guna Bangsa, 2023)
Stunting is a chronic malnutrition problem and results in irreversible growth disturbances for toddlers. One of the causes of stunting is maternal factors that occur during pregnancy and after the child is born. This study aims to analyze the association between maternal factors that influence stunting prevention behavior using the Health Promotion Model. The research method uses an analytic survey with a cross sectional approach, which was conducted in RW 4 Curug Village, Depok City. The number of samples are 110 mothers, using a purposive sampling. Data analysis used is path analysis with STATA 17. The results showed that there is a direct and positive association between perceived benefit and stunting prevention behavior (b = 1.45; p = 0.036). There is a direct and positive association between self-efficacy and stunting prevention behavior (b= 1.83; p < 0.001). There is an indirect and positive association between prior relate behavior and stunting prevention behavior through perceived benefit (b= 1.45; p= 0.003). There is an indirect and positive association between prior relate behavior and stunting prevention behavior through self-efficacy (b = 1.78; p < 0.001). There is an indirect and positive association between personal psychology and stunting prevention behavior through perceived benefit (b= 1.53; p= 0.001). There is an indirect and positive association between personal psychology and stunting prevention behavior through self-efficacy (b = 1.54; p = 0.001). The factors in the Health Promotion Model have a significant and positive association to stunting prevention behavior.